The Diagnosis and Treatment of a Rare Maxillary Plasmacytoma: a Case Report - Amir Mansour Shirani; Atefeh Akhani; Vahid Esfahanian; Shahab Etemadi; Mohammad Reza Mohajeri (Shiraz University of Medical Sciences, 2020)
The jaw plasmacytoma is a very rare condition, which its diagnosis is difficult in clinical routine. Up to now, less than 60 cases of jaw plasmacytoma have been reported in the literature. In the present case report, we reported a rare case of jaw plasmacytoma in a 42-year-old female, which was misdiagnosed with dental granuloma and abscess. The diagnosis of plasmacytoma was done by immunohistochemistry (IHC) evaluation following a cone beam computed tomography (CBCT) assessment. The patient was treated with radiotherapy and is disease free after 2 years.